The small airway epithelium as a target for the adverse pulmonary effects of silver nanoparticle inhalation. Issue 6 (3rd July 2018) - Guo, Chang; Buckley, Alison; Marczylo, Tim; Seiffert, Joanna; Römer, Isabella; Warren, James; Hodgson, Alan; Chung, Kian Fan; Gant, Timothy W.; Smith, Rachel; Leonard, Martin O.
Abstract: Experimental modeling to identify specific inhalation hazards for nanomaterials has in the main focused on in vivo approaches. However, these models suffer from uncertainties surrounding species-specific differences and cellular targets for biologic response. In terms of pulmonary exposure, approaches which combine 'inhalation-like' nanoparticulate aerosol deposition with relevant human cell and tissue air–liquid interface cultures are considered an important complement to in vivo work. In this study, we utilized such a model system to build on previous results from in vivo exposures, which highlighted the small airway epithelium as a target for silver nanoparticle (AgNP) deposition. RNA-SEQ was used to characterize alterations in mRNA and miRNA within the lung. Organotypic-reconstituted 3D human primary small airway epithelial cell cultures (SmallAir) were exposed to the same spark-generated AgNP and at the same dose used in vivo, in an aerosol-exposure air–liquid interface (AE-ALI) system. Adverse effects were characterized using lactate, LDH release and alterations in mRNA and miRNA. Modest toxicological effects were paralleled by significant regulation in gene expression, reflective mainly of specific inflammatory events. Importantly, there was a level of concordance between gene expression changes observed in vitro and in vivo . We also observed a significant correlation between AgNP and mass equivalent silver ion (Ag + ) induced transcriptional changes in SmallAir cultures. In addition to key mechanistic information relevant for our understanding of the potential health risks associated with AgNP inhalation exposure, this work further highlights the small airway epithelium as an important target for adverse effects.